The impact of fetuin-A on predicting aortic arch calcification: secondary analysis of a community-based survey - Lin, Yi-Hung; Lin, Meng-Hung; Shi, Chung-Sheng; Lin, Yu-Sheng; Lin, Chun-Liang; Yang, Yao-Hsu; Liao, Yu-San; Chen, Mei-Yen; Tsai, Ming-Horng; Lin, Ming-Shyan (Frontiers in Cardiovascular Medicine, 2024)
Introduction Atherosclerotic cardiovascular disease is associated with a high mortality rate due to vascular calcification. The role of fetuin-A in aortic arch calcification (AAC) is less well understood. Methods An analysis of secondary biomarkers was performed on 800 individuals from the biobank using the community database. AAC was defined by radiologists based on imaging. Multiple variables logical analysis was used for risk analysis. Results A total of 736 individual samples were collected based on age and gender. The average age is 65 ± 10 years, and half the population comprises men. In spite of similar body weight, renal function, and hepatic function, the AAC group had higher blood pressure and fetuin-A levels independently: systolic blood pressure (SBP) index ≥130 mmHg [adjusted odds ratio (aOR) 1.85, 95% confidence interval (CI) 1.34–2.57, p = 0.002] and fetuin-A (aOR 0.62, 95% CI 0.50–0.76, p < 0.001). Moreover, it is evident that AAC can be predicted more accurately when combined with SBP ≥130 mmHg and a low fetuin-A level (<358 μg/ml: aOR 5.39, 95% CI 3.21–9.08) compared with the reference. Conclusion Low fetuin-A levels are significantly correlated with AAC while there is an increased association between vascular calcification and coexisting hypertension.